Prevalence of Hepatitis B Antiviral Drug Resistance Variants in North American Patients with Chronic Hepatitis B Not Receiving Antiviral Treatment - Lok, Anna S. (J Viral Hepat, 2017)
Antiviral drug resistance HBV variants (HBV-DR) occur spontaneously in chronic hepatitis B (CHB) patients and after exposure to nucleos(t)ide analogues (NUCs). We determined the prevalence of HBV-DR variants among participants of the Hepatitis B Research Network (HBRN) Cohort Study conducted at 21 sites in the United States (US) and Canada. Samples obtained from 1342 CHB participants aged ≥18 years, and who were currently not receiving NUCs, were tested for HBV-DR variants by Sanger sequencing. In addition, next generation sequencing (NGS) was used to characterize HBV-DR variants from 66 participants with and 66 participants with no prior NUC exposure matched for HBV genotype and HBV DNA level. Half the participants were men, 75% Asian, 26% HBeAg-positive. Primary HBV-DR variants were detected by Sanger sequencing in 16 (1.2%) participants: 2/142 (1.4%) with and 14/1200 (1.2%) without prior NUC exposure; only 1 of these 16 had a secondary variant. In total, 23 (1.7%) participants had secondary variants, including 1 with prior NUC experience. In the subset of 132 participants, NGS detected HBV-DR variants in a higher proportion of participants: primary variants in 18 (13.6%) [8 (12.1%) with, and 10 (15.2%) without prior NUC therapy], and secondary variants in 10 (7.6%) participants. Based on Sanger sequencing, prevalence of primary HBV-DR variants is low (1.2%) among adults with CHB in US/Canada. The similar low prevalence of HBV-DR variants in participants with and without NUC treatment suggests transmission of these variants is uncommon.